Adaptive consensus control for nonlinear multiagent systems with unknown control directions and time-varying actuator faults - Wang, Chenliang (2022)
In this article, an adaptive consensus tracking control scheme is proposed for a class of high-order nonlinear multiagent systems with unknown control directions. Different from the existing results, the unknown control directions are not required to be identical and also unknown time-varying actuator faults are taken into account simultaneously. We design some novel Nussbaum functions and construct a monotonously increasing sequence in which the effects of our multiple Nussbaum functions reinforce rather than counteract each other. Moreover, some integrable auxiliary signals and a novel contradiction argument are introduced in the design and analysis. With these efforts, the obstacle jointly caused by the unknown control directions and actuator faults are circumvented, and the global stability of the overall closed-loop system and asymptotic convergence to zero of tracking errors are successfully achieved. Simulation results illustrate the effectiveness of the proposed control scheme.